An electrorheological elastomer with marigold-like TiO2 particles towards large tunable range of storage modulus. (1st December 2022) - Liu, Lingyun; Niu, Chenguang; Ma, Ning; Dong, Xufeng
Abstract: The tunable range of storage modulus is closely related to the performance of electrorheological elastomers (EREs). Previous studies have made great progress by adjusting the chemical composition of dielectric particles, properties of matrix and interface properties of particles/matrix, while the range of modulus variation of EREs is still narrow when the mass fraction of particles is relatively low. In this study, marigold-like TiO2 particles with complicated surface nanostructure were synthesized via a solvothermal method, and the EREs were prepared by using these particles as dispersion phase and silicone rubber as matrix. The storage modulus. The results illustrate that EREs containing marigold-like TiO2 particles (M-EREs) have large field-induced storage modulus (103.8 kPa) and significant relative ER effect (69.5%). The obvious performance results from the high crosslink density and strong friction between matrix and particles. These observations indicate a promising way to enhance the performance of EREs.